Modulation of Low-Voltage-Activated Inward Current Permeable to Sodium and Calcium by DARPP-32 Drives Spontaneous Firing of Insect Octopaminergic Neurosecretory Cells - Lapied, Bruno; Defaix, Antoine; Stankiewicz, Maria; Moreau, Eléonore; Raymond, Valérie (Frontiers in Systems Neuroscience, 2017)
Identification of the different intracellular pathways that control phosphorylation/dephosphorylation process of ionic channels represents an exciting alternative approach for studying the ionic mechanisms underlying neuronal pacemaker activity. In the central nervous system of the cockroach Periplaneta americana, octopaminergic neurons, called dorsal unpaired median (DUM neurons), generate spontaneous repetitive action potentials. Short-term cultured adult DUM neurons isolated from the terminal abdominal ganglion of the nerve cord were used to study the regulation of the low-voltage-activated channel permeable to sodium and calcium (Na/Ca), involved in the pre-depolarization, under whole cell voltage- and current-clamp conditions. A bell-shaped curve illustrating the regulation of the amplitude of the maintained current versus [ATP]i was observed. This suggested the existence of phosphorylation mechanisms. The PKA inhibitor, H89 and elevating [cAMP]i, increased and decreased the current amplitude, respectively. These results together with the effects of forskoline indicated a regulation of the current via a cAMP/PKA cascade. Furthermore, intracellular application of PP2B inhibitors, cyclosporine A, FK506 and PP1/2A inhibitor, okadaic acid decreased the current amplitude. From these results and because octopamine regulates DUM neuron electrical activity via an elevation of [cAMP]i, we wanted to know if, like in vertebrate dopaminergic neurons, octopamine receptor stimulation could indirectly affect the current via PKA-mediated phosphorylation of Dopamine- and cAMP-regulated Phosphoprotein-32 (DARPP-32) known to inhibit PP1/2A. Experiments were performed using intracellular application of phospho-DARPP-32 and non-phospho-DARPP-32. Phospho-DARPP-32 strongly reduced the current amplitude whereas non-phospho-DARPP-32 did not affect the current. All together, these results confirm that DARPP-32-mediated inhibition of PP1/2A regulates the maintained Na/Ca current, which contributes to the development of the pre-depolarizing phase of the DUM neuron pacemaker activity.